Scientific Articles and Publication Training for English Teachers of SMP and SMA in Rokan Hulu: Pelatihan Penulisan dan Publikasi Artikel Ilmiah Bagi Guru Bahasa Inggris SMP dan SMA di Rokan Hulu - Batdal Niati; Evi Kasyulita; Ummi Rasyidah; Pipit Rahayu; Andri Donal; Eripuddin Eripuddin; Rivi Antoni; Wirda Jannatul Jannah (Yayasan Ahmar Cendekia Indonesia, 2022)
In writing and publication of scientific articles, lecturers need to be present to train teachers. This is in line with the task of lecturers in implementing the Tridharma of higher education and the main performance indicators; lecturers work outside the campus. Therefore, all lecturers of the English department of Universitas Pasir Pengaraian contributed to help English teachers in Rokan Hulu in writing and publishing scientific articles. The objectives of the service activities are:(1)to increase teachers’ understanding and competence in writing scientific articles;(2)to provide assistance to teachers in writing scientific articles;(3)to increase teachers' understanding of how to publish scientific articles. The number of participants for the first activity were 25 English teachers SMP and 80 English teachers for the second activity. The results of the activities were that the teacher can write articles starting from writing article identities, abstracts, introductions, citations and references, methods, presentation of results and discussions, understanding of using the Mandeley application. Although it had not been proven that articles had been published, the teachers already known and understood the procedures for publication on journals and proceedings. Abstrak Dalam penulisan dan publikasi artikel ilmiah, dosen perlu hadir untuk melatih guru. Hal ini sejalan dengan tugas dosen dalam pelaksanaaan tridarma perguruan tinggi dan indicator kinerja utama; dosen berkegiatan diluar kampus. Maka, semua dosen prodi Pendidikan Bahasa Inggris Universitas pasir pengaraian berkontribusi membantu guru Bahasa inggris di Rokan Hulu dalam penulisan dan publiksai artikel ilmiah. Tujuan kegiatan pengabdian adalah:(1) meningkatkan pemahaman dan kompetensi guru dalam penulisan artikel ilmiah;(2) melakukan pendampingan kepada guru dalam menulis artikel ilmiah;(3) meningkatkan pemahaman guru tentang cara publikasi artikel ilmiah. Jumlah Peserta kegiatan pertama yaitu 25 guru Bahasa inggris SMP dan peserta kegiatan kedua 80 guru Bahasa inggris SMA. Hasil kegiatan yaitu guru sudah bisa menulis artikel dimulai dari penulisan identitas artikel, abstrak, pendahuluan, pengutipan dan referensi, metode, penyajian hasil dan diskusi, paham menggunakan aplikasi mandeley. Meskipun belum terbukti sudah publikasi artikel, para guru sudah mengetahui dan memahami tata cara publikasi pada jurnal maupun prosiding.